2020
DOI: 10.1080/1943815x.2020.1825227
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nitrous oxide emission factors for arable and grassland ecosystems

Abstract: We quantified seasonal nitrous oxide (N 2 O) emissions and the associated emission factors (EFs) from: (i) winter oilseed rape (WOSR) cultivated under conventional tillage (CT) and strip tillage (ST) at four fertilizer rates (0, 160, 240 and 320 kg N ha −1) in 2014/ 2015, and (ii) grassland plots receiving no fertilizer (0 kg N ha −1), or mineral nitrogen (67 kg N ha −1), and either cattle or pig slurry (50, 100 and 200 m 3 ha −1). Greater fluxes were observed at higher soil temperatures and a higher water fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Tillage management had little impact on N 2 O emissions in this study (Table 2 and Table 3) in line with earlier work examining CT and RT systems (Abdalla et al, 2010;Liu et al, 2016). Peak N 2 O emissions that were found in the MT and ST but not in the CT treatments coincided with a higher WFPS (>70%) and higher temperatures (>10°C) as noted in previous studies (Adviento-Borbe et al, 2007;Abdalla et al, 2010;Žurovec et al, 2017;O'Neill et al, 2020). This indicates that denitrification is the main source of N 2 O production and the N 2 O emissions are largely dependent on the extent of soil anaerobiosis.…”
Section: Crop Management and Ghg Emissionssupporting
confidence: 90%
See 2 more Smart Citations
“…Tillage management had little impact on N 2 O emissions in this study (Table 2 and Table 3) in line with earlier work examining CT and RT systems (Abdalla et al, 2010;Liu et al, 2016). Peak N 2 O emissions that were found in the MT and ST but not in the CT treatments coincided with a higher WFPS (>70%) and higher temperatures (>10°C) as noted in previous studies (Adviento-Borbe et al, 2007;Abdalla et al, 2010;Žurovec et al, 2017;O'Neill et al, 2020). This indicates that denitrification is the main source of N 2 O production and the N 2 O emissions are largely dependent on the extent of soil anaerobiosis.…”
Section: Crop Management and Ghg Emissionssupporting
confidence: 90%
“…Emissions of N 2 O and CH 4 were measured using the manual closed chamber method (Chadwick et al, 2014). Accumulation of N 2 O within the chamber headspace, measured at four time points over 1 hour (T 0 , T 20 , T 40 , T 60 ), was determined to be linear on 84% of occasions (O'Neill et al, 2020). The unvented chambers (above) were sealed onto the collars for an enclosure period of 40 min (T 40 ) and sampling carried out between 9.00 and 13.00 h (Barton et al, 2015).…”
Section: Soil Co 2 N 2 O and Ch 4 Emission Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low N 2 O‐N EFs observed in this study are not uncommon, as previous studies on temperate grasslands have reported low N 2 O EFs (<0.5%) for organic N inputs (Reinsch et al, 2020; Voglmeier et al, 2019). For example, Irish grasslands receiving 160–640 kg N ha −1 year −1 cattle slurry emitted only −0.20% to 0.43% of the applied N (O'Neill et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This Special Issue contains a selection of contributions to the symposium. It consists of this overview and seven topical papers as illustrative examples of the scientific results presented at the symposium (Wilson and Scholes 2020;O'neill et al 2020;Godwin and Ferenchiak 2020;Howarth 2020;Laban et al 2020;Verchot et al 2020;Zou and Osborne 2020). In the following section, we give an impression of the seven contributions.…”
Section: Diversity and Complexitymentioning
confidence: 99%